THE EFFECTIVENESS OF WORD WALL STRATEGY TO TEACH WRITING DESCRIPTIVE TEXT FOR TENTH GRADERS IN SMA AL-AMIN PACIRAN (RETAIN, 2016)
THE EFFECTIVENESS OF WORD WALL STRATEGY TO TEACH WRITING DESCRIPTIVE TEXT FOR TENTH GRADERS IN SMA AL-AMIN PACIRAN Novita Sari English Education, Language and Art Faculty, State University of Surabaya novitasari2@mhs.unesa.ac.id Drs. Fahri, M.A. English Education, Language and Art Faculty, State University of Surabaya fahri@unesa.ac.id Abstrak Siswa di kelas menulis sering mengalami kesulitan dalam menyusun teks deskriptif. Masalah ini disebabkan oleh lemahnya kreativitas siswa dalam menuangkan idenya. Oleh karena itu, word wall strategi digunakan untuk memotivasi siswa dalam membangun ide dalam menulis teks deskriptif. Word wall adalah strategi yang bisa digunakan untuk mengajar menulis teks descriptive. Strategi ini memberikan kata kunci kepada untuk mengembangkan ide mereka dengan mudah. Kata kunci tersebut memberikan pancingan atau klu bagi siswa untuk menyusun kata lain yang berkaitan dengan kata kunci berdasarkan kata-kata mereka sendiri, kemudian mereka harus membuat kalimat untuk menciptakan teks yang baik dari kata kunci dan kata-kata mereka. Kalimat tersebut harus berisi kata-kata sesuai dengan kata kunci dan kata-kata mereka yang berkaitan satu sama lain. Eksperimental design digunakan dalam penelitian ini yang bertujuan untuk menemukan perbedaan yang signifikan dalam nilai hasil menulis siswa antara siswa yang diajar menggunakan word wall strategi dan siswa yang diajar menggunakan buku dan papantulis. Hasil yang diperoleh menunjukkan bahwa nilai rata-rata dari control grup pada pre-tes adalah 71.20 (SD = 4.62781) dan eksperimental grup adalah 70.80 (SD = 4.93288). Pada pos-test nilai rata-rata dari control grup adalah 74.40 (SD = 3.62859) dan eksperimental grup adalah 78.00 (SD = 5.40062). Data tersebut menunjukkan bahwa nilai post-test dari eksperimental grup lebih besar dari nilai post-test control grup dengan nilai eta square adalah .0137 (moderate effect) yang berarti bahwa word wall strategi memberikan efek yang moderat pada kemampuan menulis deskriptif teks siswa. . Kata Kunci: menulis, teks deskriptif, strategi word wall. Abstract Students in the writing class often find difficulties in composing descriptive text. This problem is caused by the lack of students’ creativity in exploring ideas. Therefore, Word Wall strategy is needed to motivate students to be able to build up ideas in writing descriptive text. Word wall is a strategy that can be used for teaching writing descriptive. This strategy gives key words for students to develop their ideas easily. The key word gives trigger for the students to arrange another word which is relevant with the key word based on their own words, then they should make sentences to create a good text from those key word and their own words. The sentences should consist of the key word and their own words that is related each other. Experimental research design is used in this study was aimed to find out the significant difference in term of students’ writing scores between students who are taught by using Word Wall Strategy and those who are taught by using book and whiteboard. The result which was gotten shows that the mean score of control group in pre-test was 71.20 (SD = 4.62781) and experimental group was 70.80 (SD = 4.93288). The post-test mean scores of control group was 74.40 (SD = 3.62859) and experimental group was 78.00 (SD = 5.40062). The number shows that the post-test score of experimental group was higher than post-test score of control group with Eta Square value was .0137 (moderate effect) which means that the word wall strategy had moderate effect on students’ descriptive text writing ability. Keywords: writing, descriptive text, word wall strategy.